Treatment of spinal osteoporosis in postmenopausal women. - Nordin, B E (1980)
Ninety-five postmenopausal women with unequivocably wedged or compressed vertebrae in whom the recognised causes of secondary osteoporosis had been excluded were studied, 41 having no treatment and the rest one or more of six different treatments. The treatment regimens comprised calcium supplements, vitamin D, calcium and vitamin D, ethinyloestradiol or--where oestrogens were contraindicated--norethisterone, 1 alpha-hydroxycholecalciferol (1 alpha-OHD3), or hormones with 1 alpha-OHD3. The seven groups were reasonably comparable in most respects except that the hormone-treated patients were younger and had a higher initial cortical area ratio than the others, and the calcium- and hormone-treated groups had the best initial radio-calcium absorption. The untreated osteoporotic patients lost cortical bone more rapidly than do normal postmenopausal women. Three treatments (calcium, hormones, and 1 alpha OHD3 plus hormones) appear to be useful in modifying the disease, and two treatments (vitamin D and 1 alpha-OHD3) useless or even harmful. Vitamin D and 1 alpha-OHD3 are more safely used in conjunction with oestrogens, which protect bone against resorption, than on their own.